Collapsible Behavior of Lateritic Soil Due to Compacting Conditions - Silveira, Isabela Augusto [UNESP]; Rodrigues, Roger Augusto [UNESP] (Springer Nature, 2020)
Soil collapse is a major geotechnical problem that causes architectural and structural damage to buildings and engineering infrastructure. Losses due to soil collapsibility have an economical aspect and the study of these soils is very important due to the large occurrence of collapsible soils around the world. In this research, conventional oedometer tests and suction-controlled oedometer tests were conducted to study the benefit of compaction as a method of improving the behavior of a lateritic soil that is particularly susceptible to collapse after soaking. The results offer practical information to minimize problems arising from collapsible soils. The soil water content before the sample is inundated affected the soil collapsible behavior. Soil specimens less dense when compacted at the dry side of the compaction curve exhibited volume variation under loading less than 4% and collapse deformations up to about 11% when exposed to flooding, while soil specimens compacted at optimum moisture content showed volume variation under loading around 10% and a maximum collapse deformation by about 6%. The collapse deformations changed significantly with inundation stress for the soil compacted especially for stresses above 100 kPa. The collapse deformations were almost insignificant when the lateritic soil had a relative compaction of 90% with values almost always less than or equal to 2%, proving that the compaction process is a soil improvement technique that can significantly reduce the collapse induced by inundation.
Keywords: Compacted soil; Soil collapse; Suction; Unsaturated soil